TEACHING STRATEGIES TO CONTROL UNCONDUCIVE CLASS IN THE RON CLARK STORY: A FILM BY RANDA HEINES - Nuriadi; Muhammad Isranul Hakim; Nur Ahmadi; Husnul Lail (UIBU, 2023)
Although there are many teaching strategies that teachers can use, the majority of teachers employ the same strategies regardless of the students' varying needs and abilities in the classroom. Analyzing teaching strategies can be done in a variety of settings, including a real-life situation like a classroom or institution, as well as through literary works. One of the literary works is a movie for instance, the motivational movie titled The Ron Clark Story. The researcher selected descriptive qualitative research as the research design to support this study. The purpose of the study is to describe the teaching strategies used by Ron Clark to control the unconducive class and analyze the disruptive behavior dealt with by Ron Clark. The research showed that, according to Korpershoek et al.'s theory of teaching strategies, Ron Clark's method of teaching in the movie was made up of two teaching strategies. Both preventive and reactive strategies are available. Additionally, Ron Clark preferred the reactive strategy, which appeared 10 times, to the preventive strategy, which appeared 9 times. Then, in accordance with Cangelosi’s theory, Ron Carlk also addressed both violent and nonviolent disruption. non-violent disruption accounted for 7 scenes of the most disruptive conduct, whereas violent disruption accounted for 6.